2019
DOI: 10.21873/invivo.11733
|View full text |Cite
|
Sign up to set email alerts
|

Use of Droplet Digital Polymerase Chain Reaction for Detecting Minimal Residual Disease: A Prospective Multi-Institutional Study

Abstract: Background/Aim: Droplet digital polymerase chain reaction (ddPCR) is an exact method of measuring nucleic acids. The aim of this prospective study was to evaluate minimal residual disease (MRD) using ddPCR in chronic myeloid leukemia (CML) patients. Patients and Methods: Between May 2013 and November 2014, CML patients treated with nilotinib were enrolled in our study. BCR/ABL1 transcripts levels were evaluated using ddPCR at the first time of complete molecular response (CMR). We enrolled 15 patients from 7 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…This enables precise detection of a PCR product and absolute quantification of MRD levels without any external standard curve. 4 In several studies, a comparable accuracy and sensitivity of ddPCR to qPCR was confirmed with high concordance between both methods for different lymphoproliferative disorders. [3][4][5][6][7][8] Della Starza et al recently examined the sensitivity of MRD quantification using ddPCR for pediatric ALL.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…This enables precise detection of a PCR product and absolute quantification of MRD levels without any external standard curve. 4 In several studies, a comparable accuracy and sensitivity of ddPCR to qPCR was confirmed with high concordance between both methods for different lymphoproliferative disorders. [3][4][5][6][7][8] Della Starza et al recently examined the sensitivity of MRD quantification using ddPCR for pediatric ALL.…”
Section: Introductionmentioning
confidence: 77%
“…Even though different groups established ddPCR assays for various hematologic malignancies, they all concluded that ddPCR was well suited for MRD determination 3–27 . For a detailed overview about different ddPCR approaches for MRD detection, see Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…qPCR is another molecular‐based method for MRD identification 171 . A comparative study by Lenczowsk et al showed that dPCR method is more accurate than qPCR in MPN patients MRD detection 172–174 . The residuals of disease give disappointing results of allogeneic transplantation and increase the risk of recurrence 21 .…”
Section: The Role Of Exosomes As Potential Marker For Mrdmentioning
confidence: 99%